2023
DOI: 10.3390/antiox12051007
|View full text |Cite
|
Sign up to set email alerts
|

Radical Scavenging and Cellular Antioxidant Activity of the Cocoa Shell Phenolic Compounds after Simulated Digestion

Abstract: The cocoa industry generates a considerable quantity of cocoa shell, a by-product with high levels of methylxanthines and phenolic compounds. Nevertheless, the digestion process can extensively modify these compounds’ bioaccessibility, bioavailability, and bioactivity as a consequence of their transformation. Hence, this work’s objective was to assess the influence of simulated gastrointestinal digestion on the concentration of phenolic compounds found in the cocoa shell flour (CSF) and the cocoa shell extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…These correlations were also significant with p < 0.01 for HOCl and p < 0.001 for both ONOO − assays. Therefore, the remarkable contribution of phenolic compounds abundantly produced in CS to its bioactivity was highlighted by the strong positive correlations determined and corroborated by previous studies with identical outcomes on other food by-products [24,25,37,38,40,41].…”
Section: Screening Of Potential Correlations Between Phenolic Composi...supporting
confidence: 82%
See 1 more Smart Citation
“…These correlations were also significant with p < 0.01 for HOCl and p < 0.001 for both ONOO − assays. Therefore, the remarkable contribution of phenolic compounds abundantly produced in CS to its bioactivity was highlighted by the strong positive correlations determined and corroborated by previous studies with identical outcomes on other food by-products [24,25,37,38,40,41].…”
Section: Screening Of Potential Correlations Between Phenolic Composi...supporting
confidence: 82%
“…The findings on ROS/RNS scavenging efficiency pointed out the promising role of phenolic composition in the bioactivity of digested and undigested CS (particularly hydroxybenzoic acids, hydroxycinnamic acids, flavanols, flavonols, and lignans), whose counteracting responses have been attested in recent research [27,41,42].…”
Section: Scavenging Activity Against Reactive Oxygen and Nitrogen Spe...mentioning
confidence: 90%
“…Furthermore, we recently demonstrated that the main phenolic compounds persisted after simulated gastrointestinal digestion, indicative of their capacity to reach plasma. We also observed that the digested fraction exhibited a free-radical scavenging capacity, counteracting oxidative stress in culture cells [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Foods or food ingredients with antioxidant properties are of particular interest since oxidative stress is one of the underlying mechanisms implicated in hypertension and CVD [ 27 , 28 ], which is also a hallmark of aging [ 29 ]. The composition of CSE and its antioxidant actions, demonstrated in vitro , in cell cultures, and in arteries [ 15 , 24 ], suggests that this extract is a suitable ingredient for targeting hypertension and associated CVD. As an experimental model, we used rats exposed to undernourishment conditions during fetal life, induced by maternal undernutrition during gestation (MUN rats).…”
Section: Discussionmentioning
confidence: 99%